The World Health Organization's External Quality Assurance System Proficiency Testing Program Has Improved the Accuracy of Antimicrobial Susceptibility Testing and Reporting among Participating Laboratories Using NCCLS Methods - Chaitram, Jasmine M. (American Society for Microbiology, 2003)
A total of 150 laboratories in 33 countries that followed the NCCLS testing procedures participated in the World Health Organization's External Quality Assurance System for Antimicrobial Susceptibility Testing (EQAS-AST) from January 1998 through March 2001. Laboratories tested seven bacterial isolates for antimicrobial resistance and reported the results to the Centers for Disease Control and Prevention (CDC) in Atlanta, Ga. The results were compared to the results generated at the CDC with the NCCLS broth microdilution and disk diffusion reference methods. Although there were few testing errors with Salmonella enterica subsp. enterica serovar Enteritidis, drugs that are not appropriate for therapy of Salmonella infections were tested and reported by 136 (91%) of 150 laboratories. In addition, 29 (20%) of 150 laboratories used the Staphylococcus aureus breakpoints to report oxacillin results for Staphylococcus saprophyticus. For a vanB-containing Enterococcus faecalis strain, 124 (83%) of 150 laboratories correctly reported vancomycin results that were ±1 doubling dilution from the reference MIC or ±3 mm from the reference disk diffusion result. Of the laboratories that tested Streptococcus agalactiae by disk diffusion, 17% reported nonsusceptible results for penicillin in error. While 110 laboratories (73%) tested the S. pneumoniae challenge isolate against a fluoroquinolone, 83% tested it against ciprofloxacin, for which there are no NCCLS interpretive criteria. Ten of 12 laboratories testing levofloxacin and 4 of 4 laboratories testing ofloxacin by an MIC method correctly reported resistant results for the isolate. Feedback letters sent to participating laboratories highlighted areas of susceptibility testing in individual laboratories that needed improvement. The positive impact of the feedback letters and the overall effectiveness of the EQAS program were documented in repeat testing challenges with pneumococci and staphylococci. The 31 and 19% increases in the numbers of laboratories using appropriate testing methods for pneumococci and staphylococci, respectively, in 2000 versus 1998 indicate that laboratory performance is improving.